(untitled) (Pulse, 2017)
A fifteen and a half years old adolescent boy was referred by the psychiatrist to the Child Development Centre (CDC) for an evaluation of his mental status as he was stubbornly resisting to take medication in spite of regular counselling efforts. This boy presented with school refusal with manifestations of Obsessive Compulsive Disorder (OCD) with a complicated family dynamic to the psychiatrist. His interesting atypical development in early childhood led to clinicians concern of excluding Autism Spectrum Disorder (ASD). He was finally diagnosed and jointly managed as a case of High Functioning Autism (HFA) with co-morbid conditions by a joint multidisciplinary team approach of CDC and Psychiatry Department of AHD. Pulse Vol.9 January-December 2016 p.64-68